The Implementation of Family Hope Program in Social Protection and Welfare in West Lombok - Ahmad Amir Aziz; Royani Royani; Syukriati Syukriati (AIBPM Publisher, 2021)
Social inequality remains a crucial problem in Indonesia. This paper intends to describe the implementation of the Family Hope Program as social protection and its impact on improving family welfare in West Lombok. This qualitative research used an analytic descriptive approach, with a case study in the village of Terong Tawah. The results of the study show that the program beneficiaries can experience welfare, manage family finances well, and meet what they need, not what they want. In addition to guaranteed health services, they are kept safe from a school dropout, especially for pregnant and breastfeeding women, as well as toddlers and children.